A needle-like cobalt-based bifunctional catalyst supported on carbon materials for effective overall water splitting. (15th November 2021) - Tang, Tao; Li, Xijie; Feng, Zhanhui; Liu, Yingju
Abstract: Nowadays, hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) dual-functional electrocatalyst in the field of water electrolysis has great advantages in reducing costs and simplifying electrolytic cell installations. Herein, Co–Mo particles were electrodeposited on the carbon nanotubes (CNTs)/reduced graphene oxide (rGO)-modified copper foam to form the Co–Mo-CNTs/rGO-copper foam (CF), then it was subjected to a certain potential for alkaline etching, thus needle-like E-Co–Mo-CNTs/rGO-CF was synthesized. Results showed that the material surface mainly formed by the interlacing of Co oxide was more conducive to capturing the intermediates in the HER/OER reaction, while the CNTs/rGO-CF structure was closely connected to the metal layer, making excellent performance of total hydrolysis in KOH. The electrocatalyst exhibited remarkable electrocatalytic activity for HER and OER in 1 M KOH, requiring only 71 and 268 mV overpotential to drive 10 mA·cm −2, respectively. Especially, only a battery voltage of 1.52 V was needed to drive 10 mA·cm −2 in two-electrode system for overall water splitting. This work provides a method for the construction of dual-functional electrocatalyst that combined carbon materials and metals.